Lower Eyelid Transcutaneous Blepharoplasty, Minimizing Complications and Correction of Lower Eyelid Malposition - Yapa, Sharinie; Raghavan, Ullas (Facial Plastic Surgery, 2022)
The periocular area is one of the first and most noticeable areas affected by ageing. Common signs of lower lid ageing include rhytids, prominent eye bags caused by prolapse of orbital fat pads, increased lid laxity leading to lid malpositioning, and deepening of tear troughs, all of which give a sunken aged appearance. Lower lid transcutaneous blepharoplasty can correct most of these problems providing excellent long-term aesthetic outcomes with minimal downtime for the patient. However, lower eyelid anatomy is complex, and a thorough understanding of its structure and function is needed to avoid serious complications such as lid malpositioning and blindness. In this review, we present the anatomy of the lower lid and useful surgical techniques to circumvent and avoid such complications.
Keywords: anatomy; lower eyelid; transcutaneous blepharoplasty; surgical techniques; complications